Abundant transcription of a cellular gene in T cells infected with human T-cell leukemia-lymphoma virus. - Manzari, V (1983)
Human T-cell leukemia-lymphoma virus (HTLV) is a type C retrovirus associated with a subtype of mature T-cell malignancy in humans. HTLV also infects normal human cord blood mature T lymphocytes in vitro and induces a number of phenotypic changes in these cells, including their continuous growth and partial or complete independence of T-cell growth factor (TCGF). As part of our initial study designed to analyze gene(s) specifically activated by HTLV infection, we have isolated a recombinant DNA clone by differential screening of a cDNA library made from mRNA of a human T-cell lymphoma cell line producing HTLV. This cDNA identifies a single-copy gene in all human DNAs and a single mRNA species of 2.3 kilobases expressed at several hundred copies per cell in five HTLV-positive neoplastic T-cell lines. In addition, cord blood T lymphocytes infected with HTLV, but not the uninfected counterparts, express high levels of mRNA from this gene. A survey of different human hematopoietic cell types showed that this gene is expressed at low or undetectable levels (less than 10 copies) in human T, B, myeloid, or erythroid cell lines; in moderate amounts in lymphoid precursor (immature) cell lines; and in high amounts in lectin-activated mature T-cells, comparable to those of HTLV-infected T-cell lines. The precise function of this gene has not yet been determined.